2022
DOI: 10.3390/ma15165682
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Enhancement by Laser Shock Treatment in Chromium-Alloyed Steam Turbine Blades

Abstract: In-service turbine blade failures remain a source of concern and research interest for engineers and industry professionals with attendant safety and economic implications. Very high-pressure shock impacts from laser shots represent an evolving technique currently gaining traction for surface improvement and failure mitigation in engineering components. However, the physical characteristics and effects of parameter variations on a wide range of materials are still not fully understood and adequately researched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The outcomes enable decision-makers to capture the varying component conditions in one infrastructure system (i.e., stormwater drainage system) and depict the aggravated adverse impacts on its interdependent infrastructure system (i.e., road transport system) after a hazard has occurred. The continuous advancement and development of high-performance computing technology according to [26] and [27] has opened up vistas of new possibilities and opportunities in applied scientific research, paving the way for deeper investigations than as witnessed in the past. This has also found application in flood modelling and management as demonstrated by [28] in their assessment of dual-drainage modelling to determine the effects of green stormwater infrastructure on roadway flooding and traffic performance using microscopic flow simulations to examine the specific hazard of roadway flooding and the effects of flooding on traffic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The outcomes enable decision-makers to capture the varying component conditions in one infrastructure system (i.e., stormwater drainage system) and depict the aggravated adverse impacts on its interdependent infrastructure system (i.e., road transport system) after a hazard has occurred. The continuous advancement and development of high-performance computing technology according to [26] and [27] has opened up vistas of new possibilities and opportunities in applied scientific research, paving the way for deeper investigations than as witnessed in the past. This has also found application in flood modelling and management as demonstrated by [28] in their assessment of dual-drainage modelling to determine the effects of green stormwater infrastructure on roadway flooding and traffic performance using microscopic flow simulations to examine the specific hazard of roadway flooding and the effects of flooding on traffic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the advantages of LSP over other strengthening methods, researchers have applied LSP to steam turbine blades. For example, simulation and experimental investigations by Fameso F [31] revealed that the energy intensity of LSP was the main influencing factor for increasing the residual stress in blade materials. In addition, Sundar R [32] found that the depth of the residual stress layer generated in the blade root after LSP treatment was more than 900 µm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sundar R [32] found that the depth of the residual stress layer generated in the blade root after LSP treatment was more than 900 µm. However, though the blade material introduced a large residual stress after LSP, researchers [31][32][33][34] did not perform fatigue experiments on the strengthened blade material to verify its fatigue life, indicating the need for further research on the influence of LSP.…”
Section: Introductionmentioning
confidence: 99%
“…According to [2], as opposed to experimental set-ups which are relatively costly and mostly invariable, flexible, time-saving computational models have made the prediction of mechanical effects and responses of metallic materials to laser shot impacts more robust and in-depth, with a wider spectrum of laser peening phenomena now opened for investigation.…”
Section: Introductionmentioning
confidence: 99%